1999
DOI: 10.1097/00005537-199906000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold proteoglycans and their influence on biomechanics

Abstract: Proteoglycans, particularly hyaluronic acid, play important roles in determining biomechanical properties of tissue oscillation. Future research will likely make these proteins of important therapeutic interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
279
0
17

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(304 citation statements)
references
References 33 publications
8
279
0
17
Order By: Relevance
“…Decorin is a small chain proteoglycan, which is normally distributed in the superficial layer of the lamina propria of human vocal folds. 17 Decorin acts to regulate collagen fibrils and also inhibits formation of collagen fibers 15 , suggesting that decorin may reduce scar effects. A rabbit study reported a decrease of decorin in two-month scars of rabbit vocal folds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decorin is a small chain proteoglycan, which is normally distributed in the superficial layer of the lamina propria of human vocal folds. 17 Decorin acts to regulate collagen fibrils and also inhibits formation of collagen fibers 15 , suggesting that decorin may reduce scar effects. A rabbit study reported a decrease of decorin in two-month scars of rabbit vocal folds.…”
Section: Discussionmentioning
confidence: 99%
“…Elastica-van-Gieson staining was used to identify collagen and elastin, and Alcian blue staining was used for HA after digestion with hyaluronidase. This technique was developed by Gray et al 15 to correctly identify HA in the vocal fold lamina propria. To perform hyaluronidase digestion, 50 mg of bovine testicular hyaluronidase (Sigma, St Louis, MO) was diluted in 100 mL of phosphate-buffered saline (PBS) and sections were incubated in the PBS-hyaluronidase mixture for 1 hour at 37 o C. Then the sections were stained with Alcian blue (pH 2.5).…”
Section: Histologic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pilot clinical trial hyaluronic acid-based (HA) scaffolds (HYAFF Ò 11) were used as a cell-carrier material. This naturally occurring polysaccharide is a major component of the ECM in connective tissues [15], plays a prominent role in cellular behaviour and exerts an important mechanical role [16]. Being a polysaccharide and not a protein it is potentially less antigenic, which is an important property when considering clinical uses.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we examined (i) the actions of the dynamic strain on IL-1β-induced proinflammatory gene induction in vocal fold fibroblasts, (ii) the time, magnitude, and frequency-dependent effects of dynamic mechanical signals on vocal fold fibroblasts, and (iii) the actions of dynamic strain on the production of collagen type I (alpha1) required for tissue repair and critical for the biomechanical properties of the vocal folds in the presence or absence of IL-1β. 25,26 Understanding the actions of mechanical signals on vocal fold fibroblasts would facilitate the development of therapeutic strategies to enhance resolution of vocal fold inflammation and wound healing following injury, based on sound scientific evidence.…”
Section: Introductionmentioning
confidence: 99%